Impact of Covid-19 Pandemic on Food Consumption in Indonesia - Amalia Zaida (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Prevention of Covid-19 transmission by increasing immunity of the body with protein intake results in changes in people's dietary behavior. Pressure due to changing environment and loss of work leads to the tendency to eat sweet foods, preserved, high in fat and salt. This study aims to determine changes in food consumption patterns in Indonesia during the Covid-19 pandemic. Use a quick assessment of empirical facts about Indonesia's ongoing impact on Covid-19. The research approach framework conceptualizes Covid-19 as a 'Cause', and its effect on changes in food consumption patterns is "Consequent". The data used in this study from study literature uses references from national and international literature. Literature materials in the form of journals, articles, books, and news that discuss the impact of the Covid-19 pandemic on people's behavior, especially food consumption behavior, which can be accessed in electronic media. Pandemic covid-19 in Indonesian society affects food consumption patterns, namely, in adults, consumption of vegetables, fruits, and spices increases. While in adolescence, consumption of sweets and fast food increases. This change in the diet affects immunity. A healthy diet increases immunity and reduces the potential for contracting covid-19. Changes in different diets require a tailored approach to community nutrition fulfillment programs. It is necessary to create a program to raise awareness among young people to implement a healthy diet, and a program to support the consistency of healthy diets that have been formed in the community due to the covid-19 pandemic.